AVALIAÇÃO DA AÇÃO DO EXTRATO DAS FOLHAS DE Persea americana Mill. NA REGENERAÇÃO DE FRATURA ÓSSEA - MENDONÇA, Priscylla Gouveia (2025)
Introduction: In recent years, treatments for bone fractures have advanced, but some still exhibit consolidation problems. The most common open fractures occur in the tibia in 20 to 40% of cases. The increased use of natural products, especially medicinal ones, and substances linked to phytopharmaceutical research indicate that there is great potential for the development of new medicines to treat related diseases and conditions. Objetives; To evaluate the action of the extract from the leaves of Persea americana Mill. the bone fracture repair process. Methodology: Five experimental groups with 6 animals. Healthy Group (H): no intervention; Fracture+Extract (EF): Induced fracture and oral EHPA; Fracture +Extract+ Swimming (FEN): Induced fracture, EHPA and 30 min of daily swimming; Fracture + Swimming (FN): Induced fracture, swimming for 30 min; and Fracture (F): Induced fracture. A dose of 750mg/kg of EHPA administered by oral gavage de 28 days Results: Through characterization using the liquid chromatographjy dereplication technique coupled to the mass spectrometry of the extract of Persea americana Mill. we identified 24 substances, ionized in positive and negative mode, 17 already described in the literature X-Ray confirming fracture induction on D0 and on D28 confirming bone union. The percentage of inhibition of (COX-2) in vitro, induced by EHPA, was up to 55% and was proportional to the increase in dose. Behavioral parameters, radiological effects and histology of bone tissue stained with hamatoxylin and eosin are better in groups treated with EHPA (750mg/kg).